2007
DOI: 10.1007/s10762-006-9186-4
|View full text |Cite
|
Sign up to set email alerts
|

Propagation Characteristics of Infrared Pulse Waves through Windblown Sand and Dust Atmosphere

Abstract: The physics characteristics of the windblown sand and dust atmosphere at the sand bench of Yellow River in China are discussed. The pulse distortion and time delay of infrared nanosecond pulse propagating through the atmosphere having sand and dust particles are investigated at 1.06 and 3.8 μm, respectively. It is shown that the delay of 10 ns laser pulse propagating through 5 km windblown sand and dust atmosphere are over 1 ns and 10 ns at 1.06 and 3.8 μm, respectively. The pulse spread increases slightly wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…As discussed in (Fante, 1975;Ishimaru, 1997;Kennedy, 1968), dispersion and beam spreading due to turbulent atmosphere can be neglected. Only for the very short pulses less than 100 ps proposed for high-data rate communications systems, or in extreme scenarios such as the one detailed in (Ruike et al, 2007), where sand and dust particles are likely present, pulse spreading owing to turbulent atmosphere must be included. For this latter case, physically, two possible causes exist for this pulse spreading: scattering (dispersion) and pulse wander (fluctuations in arrival time), although it is found that, under the condition of weak scattering, pulse wandering dominates the contribution to the overall broadening of the pulse Young et al, 1998).…”
Section: Generation Of Scintillation Sequencesmentioning
confidence: 99%
“…As discussed in (Fante, 1975;Ishimaru, 1997;Kennedy, 1968), dispersion and beam spreading due to turbulent atmosphere can be neglected. Only for the very short pulses less than 100 ps proposed for high-data rate communications systems, or in extreme scenarios such as the one detailed in (Ruike et al, 2007), where sand and dust particles are likely present, pulse spreading owing to turbulent atmosphere must be included. For this latter case, physically, two possible causes exist for this pulse spreading: scattering (dispersion) and pulse wander (fluctuations in arrival time), although it is found that, under the condition of weak scattering, pulse wandering dominates the contribution to the overall broadening of the pulse Young et al, 1998).…”
Section: Generation Of Scintillation Sequencesmentioning
confidence: 99%
“…Laser detection becomes more and more important in remote measurement, for its highly monochromatic and coherent, high energy density and fine time resolution [1]. Meanwhile, it is also well known that light propagating in atmosphere is highly scattered by atmospheric hydrometeors and aerosols, occasionally causing an extreme high attenuation of the received power [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%